2017
DOI: 10.1007/s00261-017-1045-3
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance elastography in the assessment of hepatic fibrosis: a study comparing transient elastography and histological data in the same patients

Abstract: MRE and TE detected liver fibrosis with comparable accuracy. In particular, the srROIs method was effective for detecting of significant fibrosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…When the stiffness cut-off values for differentiation of Ludwig stage 0-1 versus stage 2 or higher fibrosis derived from the entire population were applied to the subpopulation of patients with histologic steatosis (Fig 4), the cut-off value of 2.27 kPa had a sensitivity of 52.1% (95% CI: 39.8%, 64.5%) and specificity of 71.4% (95% CI: 60.3%, 82.6%). The cut-off value of 1.67 (1)(2)(3)(13)(14)(15)(16)(17). For identification of stage 2 or higher fibrosis, however, the performance of MR elastography in our pediatric population is less good than reported in these adult studies, where AUCs were 0.83-0.99 (1,(12)(13)(14)(15)(16)(17).…”
Section: Identification Of Significant Fibrosis: Patients With Histolmentioning
confidence: 69%
“…When the stiffness cut-off values for differentiation of Ludwig stage 0-1 versus stage 2 or higher fibrosis derived from the entire population were applied to the subpopulation of patients with histologic steatosis (Fig 4), the cut-off value of 2.27 kPa had a sensitivity of 52.1% (95% CI: 39.8%, 64.5%) and specificity of 71.4% (95% CI: 60.3%, 82.6%). The cut-off value of 1.67 (1)(2)(3)(13)(14)(15)(16)(17). For identification of stage 2 or higher fibrosis, however, the performance of MR elastography in our pediatric population is less good than reported in these adult studies, where AUCs were 0.83-0.99 (1,(12)(13)(14)(15)(16)(17).…”
Section: Identification Of Significant Fibrosis: Patients With Histolmentioning
confidence: 69%
“…In another study performed in a group of 24 healthy individuals, it was reported that the different methods had significant differences in measurement variability and that the ROI in a large liver segment had the best reproducibility, while different liver segments had significantly different stiffness values . In still another study, the choice of a single, small circular ROI was found to be superior to the freehand positioning for the detection of significant fibrosis, but the diagnostic performance was equivalent in higher fibrosis stages . In the case of large freehand positioning, the exclusion of regions with low wave propagation was shown to improve the measurement consistency, although these findings were obtained in a study with a small number of patients …”
Section: Methods For Liver and Spleen Mrementioning
confidence: 97%
“…74 In still another study, the choice of a single, small circular ROI was found to be superior to the freehand positioning for the detection of significant fibrosis, but the diagnostic performance was equivalent in higher fibrosis stages. 75 In the case of large freehand positioning, the exclusion of regions with low wave propagation was shown to improve the measurement consistency, although these findings were obtained in a study with a small number of patients. 76 Overall, the selection of the largest ROIs avoiding organ edges and large vessel structures (due to the boundary conditions they introduce), while respecting a reconstruction quality criterion, seems to be the recommended approach.…”
Section: Effect Of Region Of Interest Selectionmentioning
confidence: 95%
See 1 more Smart Citation
“…This effect was not ruled out in our study, so it might be possible that in patients with modest biliary obstruction administration of Gd-EOB-DTPA might cause a transient rise in liver stiffness. Another drawback is that no histological correlation was available; however, the purpose of our study was not to evaluate whether hepatic MRE findings correlated with clinical or histological findings (which have been assessed in several other studies [41,42]), but to compare the results within individuals' data. Furthermore, it was not possible to prove that MRI without passive driver administration really improves the quality of the examination because our study did not include MRI examinations without a passive driver.…”
Section: Discussionmentioning
confidence: 99%